A Visual Stimulus Module for P300 Based Brain Computer Interfaces - Eda AKMAN AYDIN; Inan GÜLER (International Journal of Applied Methods in Electronics and Computers, 2016)
Brain Computer Interfaces (BCIs) are the systems that provide a direct communication channel between human brain and environment. P300 potentials are involuntary brain responses which are used to control BCI systems. In order to elicit P300 responses, stimulus presentation must be provided to the users. However, t here are not common paradigms or optimal parameters for all BCI users, or all BCI applications. Using the most convenient method and parameters for each user individually will improve system performance. This study proposes a visual stimulus module for P300 based BCIs. The module offers to design stimulus interfaces based on three different stimulus interfaces, including row/column, single character and region based paradigms. The module also provides customization of the stimulus interface by setting optimal parameters for individuals practically. Furthermore, in this study, we also explained synchronization between stimulus interface and data acquisition module in detailed. In order to test the stimulus module, stimulus interfaces based on three visual stimulus paradigms were designed. All the paradigms were tested by three subjects. P300 responses yielded with three paradigms were compared by using one-way statistical analysis of variance (ANOVA) method. Preliminary results revealed that average amplitude and latency of P300 potentials that were elicited by the different paradigms may differ.